Design Recommendations for FFF Parts - Jelena Djokikj; Tatjana Kandikjan; Ile Mircheski (Springer, 2021)
Additive Manufacturing (AM) technologies since their occurrence, they are under constantly development and improvement resulting in new applications. The unique working manner of these technologies ensures them wide range of possibilities but the lack of knowledge depicts them of wide spread use. The only way fully exploit AM is to know their advantages and restrictions in other words their characteristics. Design for AM (DfAM) is the field covering all the tools, rules and guidelines developed by various authors. With this paper we are making a contribution into this field by proposing design recommendations when designing for Fused Filament Fabrication (FFF). We choose the FFF process because is the AM process with most users, according to the sold machines. We are designing samples which are analyzed for deviations in the profile and shape, and based on the results we create the design recommendations. For the fabrication of the samples we are using open-source system.